Social Media as Information and Communication Tool for Socio-Economic Empowerment of Undergraduate Students in Nigeria - Ukachi Ngozi B; Nwanna Chinwe R (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2021)
Purpose: The purpose of this work is to establish how undergraduate students in the University of Lagos and University of Nigeria, Nsukka, are using social media as information and communication tool for their socioeconomic empowerment including the specific ways in which their adoption has empowered them socioeconomically. Design/ Methodology/ Approach: The exploratory research design was adopted for the study while the simple random sampling technique was adopted in selecting undergraduate students who were seen at the lecture rooms during the lecture days. A total number of 400 third and final-year students altogether, were randomly selected from the Departments of Sociology and Mass Communication of the Faculty of Social Sciences of the two universities. A questionnaire, constructed with both open and close-ended questions was used for data collection. Findings: The findings revealed that the social media tools generally known to all the participants are; Facebook, WhatsApp, and Twitter, while the most popularly utilized ones for their socio-economic empowerment are: WhatsApp, Facebook, Twitter, Instagram, etc. The specific ways it has empowered them socio-economically include; reduction in their cost of business communication, accessing information that helped their business to blossom, advertising their products and services, and linking them up with new customers. Originality /value: This study shows how undergraduate students in the two universities are using social media as an information and communication tool for their socio-economic empowerment. It offered insight into the specific ways in which their usage has empowered them socio-economically.